Patterns of overeducation in Europe: The role of field of study - Christina Boll; Anja Rossen; Andre Wolf (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
This study investigates the incidence of overeducation among graduate workers in 21 EU countries and its underlying factors based on the European Labor Force Survey 2016 (EU-LFS). Although controlling for a wide range of covariates, the particular interest lies in the role of fields of study for vertical educational mismatch. The study reveals country and gender differences in the impact of these factors. Compared to Social Sciences, male graduates from e.g. Education, Health and Welfare, Engineering, and ICT are less and those from e.g. Services and Natural Sciences are more at risk in a clear majority of countries. These findings hold for the majority of countries and are robust against a change of the standard education. However, countries show different gendered patterns of field-specific risks. We suggest that occupational closure, productivity signals and gender stereotypes answer for these cross-field and cross-country differentials. Moreover, country fixed effects point to relevant structural differences between national labour markets and between educational systems. – – Die vorliegende Studie untersucht das Auftreten von Überqualifikation unter hochqualifizierten Beschäftigten in 21 EU-Ländern und ihre zugrunde liegenden Faktoren auf Grundlage der Europäischen Arbeitskräfteerhebung 2016 (EU-LFS). Obwohl für eine Vielzahl an erklärenden Variablen kontrolliert wird, liegt das besondere Interesse der Studie in der Rolle des Studienfaches. Die Ergebnisse zeigen, dass im Vergleich zu den Sozialwissenschaften männliche Absolventen der Studienfächer "Bildung, Gesundheit und Soziales", "Ingenieurwesen" und "Informatik und Kommunikation" ein geringeres und solche der Naturwissenschaften und Dienstleistungen ein höheres Risiko aufweisen überqualifiziert beschäftigt zu sein. Gleichzeitig weisen die verschiedenen Länder unterschiedliche geschlechtsspezifische Risikomuster auf, die auf relevante strukturelle Unterschiede zwischen den nationalen Arbeitsmärkten und zwischen den Bildungssystemen hindeuten
Keywords: J24; J21; J22; 330; Field of study; college major; overeducation; vertical mismatch; gender; realized matches; household context; EU countries; Labour Force Survey